"Ljubi Bog, kako varovati, česar ni; saj vendar pri vseh koncih in krajih sili v Mariboru slovenski značaj na dan!" - Jenuš, Gregor (Studia Historica Slovenica, 2017)
The author focuses on the mayoral term of Johann Schmiderer, the last Mayor of Maribor of the Austrian period. Schmiderer ascended to the top of the Maribor Municipal Council in 1902 and then governed it through one of the most crucial periods of its history. His term as mayor was marked by rapid economic development, electrification, as well as national struggle between the Slovenian and German population. The most significant mark was left by the Great War and the Declaration Movement that "gave birth" to the new Yugoslav state. Schmiderer managed Maribor until January 1919, when he was forced not only to abandon the mayor's office, but to hand over Maribor to the new Slovenian government.
Keywords: 20.st.; Maribor; narodnostno vprašanje; Nemci; občinska uprava; Schmiderer, Johann; Slovenci; zgodovina; župani